MODL-25. Radiation and focused ultrasound–mediated blood–brain barrier opening for DMG: safety and feasibility of combinatorial therapy. (3rd June 2022) - McQuillan, Nicholas; Tazhibi, Masih; Wei, Hong-Jian; Pouliopoulos, Antonios; Bendau, Ethan; Carrion, Andrea Webster; Berg, Alexander; Kokossis, Danae; Zhang, Xu; Zhang, Zhiguo; Englander, Zachary; Yoh, Nina; et al.
Abstract: Diffuse midline glioma (DMG) is a pediatric tumor with dismal prognosis. Systemic therapeutic strategies have been unsuccessful to date and radiotherapy (RT) remains the standard of care. A central impediment to systemic therapy is the blood-brain barrier (BBB), which precludes drug delivery to the tumor site. Focused ultrasound (FUS) with intravenous microbubbles can transiently and non-invasively circumvent the BBB to enhance drug delivery. Nevertheless, it remains unclear whether FUS is safe at the brainstem in combination with clinical doses of RT. In this study, we hypothesized that FUS-mediated BBB-opening (BBBO) is safe and feasible with 39 Gy RT. To establish a safety timeline, we administered FUS to the brainstem of nontumor bearing mice concurrent with or adjuvant to radiation; then, we validated our findings in a syngeneic orthotopic xenograft DMG model which received repeated sonication concurrent with RT. Male B6 (Cg)-Tyrc-2J/J albino mice received intracranial injection of 4423 mouse DMG cells (PDGFB+, H3.3K27M, p53−/−) at a location posterior and lateral to the lambda. A clinical RT dose of 39 Gy in 13 fractions was delivered to the brainstem with the Small Animal Radiation Research Platform (SARRP) or the XRAD-320 irradiator. FUS was administered with a 0.5 MHz transducer, and both BBBO and tumor volume were monitored with MRI. FUS-mediated BBBO in nontumor bearing mice receiving RT did not affect cardiorespiratory rate, motor function, and tissue integrity. Moreover, tumor bearing mice tolerated repeated brainstem BBBO concurrent with RT. 39 Gy over 13 fractions offered local control, although disease progression occurred in all animals approximately 3-4 weeks post-RT. Ultimately, repeated FUS-mediated BBB opening concurrent with RT is safe and feasible. In our brainstem DMG model, relapse occurs, making it ideal for future tests of combinatorial RT and FUS-mediated drug delivery.